The Orient in Utrecht (Leiden ; Boston)
xiv, 515 sayfa
Keywords: “Adriaan Reland (1676-1718), Arabist, Cartographer, Antiquarian and Scholar of Comparative Religion covers the intellectual achievements of a remarkable man: Adriaan Reland, professor of Oriental languages (1701) and Hebrew Antiquities (1713) at the University of Utrecht from 1701 to 1718. Although he never travelled beyond the borders of his home country, he had an astonishingly broad worldview. The contributions in this volume illuminate Reland's many accomplishments and follow his scholarly trajectory as an Orientalist, a linguist, a cartographer, a poet, and a historian of comparative religions. Reland, although a devout Protestant, believed that religions should be examined objectively on their own terms with the help of reliable and authentic documents, which would dispel the prejudices of the past.“ --